Environmental and Occupational Health Impact of Bauxite Mining in Malaysia: A Review - KY, Lee; LY, Ho; KH, Tan; YY, Tham; SP, Ling; AM, Qureshi; T, Ponnudurai; R, Nordin (IIUM Medical Journal Malaysia, 2017)
In the perspective of recent bauxite mining in Malaysia, this review aims to identify the potential environmental and health impacts on miners and surrounding communities. The environmental issues of bauxite mining include, air, water and soil pollution due to bauxite dust; leaching of bauxite into water sources resulting in reduced soil fertility as well as affecting agricultural food products and aquatic life. Bauxite occupational exposure affects the health of miners, and has negative consequences on the health of surrounding communities, such as increased respiratory symptoms, contamination of drinking water, other potential health risks from ingestion of bauxite and heavy metals, including noise-induced hearing loss and mental stress. This review discusses the processes of bauxite mining, its constituents and residual trace elements, and their impact on the environment and health of exposed workers and communities. It also explores the Malaysian legal requirements and standards of occupational exposure to bauxite.